Testing the effectiveness of a novel, evidence-based weight management and lifestyle modification programme in primary care: the Healthy Weight Initiative - John Baillie; Annabelle Williams; Tracy Schumacher; David Lambkin; Scott Slater (CSIRO Publishing, 2022)
Introduction Primary care prevention strategies that support and provide tools for general practice have the potential to slow and reverse rates of overweight and obesity. Aim To test the effectiveness of a novel 12-week, online, structured, evidence-based weight management and lifestyle modification programme in general practices. Methods Between August 2018 and March 2020, participants with a body mass index (BMI)  ≥ 25 were recruited from general practices in the Hunter New England and Central Coast Primary Health Network region of Australia. Practices were randomly assigned to deliver a 'low-intensity' (LI) or 'high-intensity' (HI) variant of the programme. Practitioners were trained in programme delivery. The intervention involved weekly progress and accountability checks and scripted education sessions on evidenced-based nutrition, physical activity and lifestyle modification. The trial included follow-up evaluations at 6 and 12 months. Results In total, 695 participants were recruited from 26 practices. At the end of the 12-week programme, participants in the HI treatment arm lost an average of 3.2 kg (s.d. 3.8) and 29% (50/172) achieved clinically significant weight loss (>5% of initial body weight). Positive results were maintained at evaluations by participants in the HI treatment arm who attended, but only 31% of participants at 6 months and 21% at 12 months were followed up. Discussion Participant engagement and retention and practitioner workload burden are key factors in the design of weight management programmes in primary care. Many lessons can be obtained as a result of this trial, and programme adjustments have been identified to improve its delivery model.